THE LITERARY TEXT AS A POSTMEMORY RETRAUMATIZATION (Philological Studies, 2024)
Starting from Marianne Hirsch’s thesis that the notion of postmemory can be generalised in various contexts of traumatic transfer, this paper aims to examine the interpretive validity of this concept in relation to the traumatic experience of political prisoners on Goli otok. The paper focuses on the novel Silent With the Mouth Open (Молчи со отворена уста) by the Macedonian authoress Snezana Mladenovska Angelkov, a member of the so-called postgeneration. The interpretation is focused on presenting the narrative conventions involved in articulating the postmemorial dimension in the novel, as well as its features: the elements of secondariness and of mediativeness of postmemory, as well as the (post-memorial relation to the past through imagination, projection and creation.